Infection by Streptococcus pneumoniae in children with or without radiologically confirmed pneumonia - Dafne C. Andrade; Igor C. Borges; Ana Luísa Vilas-Boas; Maria S.H. Fontoura; César A. Araújo-Neto; Sandra C. Andrade; Rosa V. Brim; Andreas Meinke; Aldina Barral; Olli Ruuskanen; Helena Käyhty; Cristiana M. Nascimento-Carvalho (Elsevier, 2018)
Objective: Community-acquired pneumonia is an important cause of morbidity in childhood, but the detection of its causative agent remains a diagnostic challenge. The authors aimed to evaluate the role of the chest radiograph to identify cases of community-aquired pneumonia caused by typical bacteria. Methods: The frequency of infection by Streptococcus pneumoniae, Haemophilus influenzae, and Moraxella catarrhalis was compared in non-hospitalized children with clinical diagnosis of community acquired pneumonia aged 2-59 months with or without radiological confirmation (n = 249 and 366, respectively). Infection by S. pneumoniae was diagnosed by the detection of a serological response against at least one of eight pneumococcal proteins (defined as an increase ≥2-fold in the IgG levels against Ply, CbpA, PspA1 and PspA2, PhtD, StkP-C, and PcsB-N, or an increase ≥1.5-fold against PcpA). Infection by H. influenzae and M. catarrhalis was defined as an increase ≥2-fold on the levels of microbe-specific IgG. Results: Children with radiologically confirmed pneumonia had higher rates of infection by S. pneumoniae. The presence of pneumococcal infection increased the odds of having radiologically confirmed pneumonia by 2.8 times (95% CI: 1.8-4.3). The negative predictive value of the normal chest radiograph for infection by S. pneumoniae was 86.3% (95% CI: 82.4-89.7%). There was no difference on the rates of infection by H. influenzae and M. catarrhalis between children with community-acquired pneumonia with and without radiological confirmation. Conclusions: Among children with clinical diagnosis of community-acquired pneumonia submitted to chest radiograph, those with radiologically confirmed pneumonia present a higher rate of infection by S. pneumoniae when compared with those with a normal chest radiograph. Resumo: Objetivos: O objetivo deste estudo foi avaliar o papel do raio-X de tórax na identificação de casos de pneumonia adquirida na comunidade (PAC) causada por agentes bacterianos. Métodos: A frequência de infecção por Streptococcus pneumoniae, Haemophilus influenzae e Moraxella catarrhalis em crianças com PAC não hospitalizadas foi comparada com a presença de confirmação radiológica da pneumonia (n = 249 crianças com pneumonia radiologicamente confirmada e 366 crianças com raio X de tórax normal). Infecção por S. pneumoniae foi diagnosticada com base na resposta sorológica a pelo menos uma dentre oito proteínas pneumocócicas investigadas (aumento ≥2 vezes nos níveis de IgG em relação a Ply, CbpA, PspA1 e 2, PhtD, StkP-C e PcsB-N ou aumento≥1,5 vezes em relação aPcpA). Infecção por H. influenzae e M. catarrhalis foi definida por aumento≥2 vezes nos níveis de IgG específica a antígenos de cada agente. Resultados: Crianças com pneumonia radiologicamente confirmada apresentaram maior taxa de infecção pelo pneumococo. Além disso, a presença de infecção pneumocócica foi um fator preditor de pneumonia radiologicamente confirmada, aumentando sua chance de detecção em 2,8 vezes (IC 95%: 1,8-4,3). O valor preditivo negative do raio X normal para a infecção por S. pneumoniae foi 86,3% (IC95%: 82,4%-89,7%). Não houve diferença nas frequências de infecção por H. influenzae e M. catarrhalis entre crianças com PAC com ou sem confirmação radiológica. Conclusões: Crianças com diagnóstico clínico de PAC submetidas a um raio X de tórax que apresentam confirmação radiológica tem maior taxa de infecção por S. pneumoniae, comparado às crianças com raio X normal. Keywords: Bacterial infection, Etiology, Lower respiratory tract infection, Radiological study, Serological tests, Palavras-chave: Infecção bacteriana, Etiologia, Infecção do trato respiratório inferior, Estudo radiológico, Testes sorológicos